The Role of Remote Sensing in Assisted Development: Experience Drawn from Work in Over 40 Countries. Issue 4 (3rd July 2016) - Ryerson, Robert; Haack, Barry
Abstract : Abstract. That there is great potential for remote sensing in development cannot be denied. As has often been said, "everything happens somewhere, " and remote sensing provides a very useful picture of everywhere. However, the use of remote sensing is often at a far lower level in broad development activities than one would expect, given its potential importance for meeting the Millennium Development Goals, Sustainable Development Goals, or the targets identified for the Post-2015 Development Agenda. Remote sensing can and should play a role in the 3 major stages of development assistance: identification of the need, program development and execution, and postcompletion program assessment and evaluation. This is so for almost all development activities involving resources, land, water, or the environment. There are a number of considerations and factors that, when taken together, explain the relatively low use of remote sensing in development. This study examines these considerations and factors drawing on the work, experience, and observations of the authors in more than 40 developing countries over the past 30 years. The authors have worked in the area of remote sensing and development in Africa, Asia, South America, and the Pacific. With better understanding of these factors it is hoped that the benefits that have long been promised by the remote sensing community will be delivered.